Emerging trends of research on mRNA vaccines: A co-citation analysis - Juan Chen; Ting Zhang; Yan Lu; Xiaoyi Yang; Zhaolian Ouyang (Taylor & Francis Group, 2022)
This study was designed to evaluate the emerging trends of research on mRNA vaccines. Altogether 3056 research articles related to mRNA vaccines published since 2010 were retrieved from the Web of Science database, based on which a co-citation analysis was conducted using CiteSpace. A total of 12 clusters were derived, all of which were classified into three periods according to the content and publication time of articles: (1) The preliminary exploratory period before early 2010s, when the potential of mRNA to induce immune response was evaluated; (2) the growing up period from early 2010s to 2019, when the stability and immunogenicity of mRNA vaccines were improved and the clinical development of products were pushed forward; (3) the rapid maturity period after the outbreak of COVID-19, when two products for COVID-19 were authorized for the first time. The approval of COVID-19 vaccines is an encouraging start, while the enormous potential of mRNA vaccines remains to be explored. Future research on mRNA-based infectious disease vaccines will focus on further optimizing mRNA modification and delivery, solving problems of the approved vaccines in real world, investigating mRNA vaccines for other infectious indications, and developing self-amplifying or thermostable vaccines. Future research on mRNA-based therapeutic cancer vaccines will focus on screening proper neoantigens, enhancing the delivery of mRNA into antigen-presenting cells and overcoming suppressive tumor microenvironment.